Optimized wet-proofed CuO/Al2O3 catalysts for the oxidation of phenol solutions: Enhancing catalytic stability - Massa, Paola Andrea (2009)
An optimized wet-proofed catalyst was prepared by successive immersion steps of conventional 37% CuO/γ-Al2O3 samples in a polytetrafluorethylene fibres suspension. Conventional and hydrophobic catalysts were tested for the oxidation of phenol solutions (5 g/L), at 140 °C and 7 atm of oxygen pressure, in a trickle bed reactor. For the conventional catalyst, phenol conversion decreased with reaction time. However, for the wet-proofed catalysts, phenol conversion levels remained almost constant with usage. The hydrophobic layer improved catalyst stability: prevented the formation of domains with cuprous species, minimized the solubilization of Cu2+ and the formation of bohmite phase during reaction.